DYNAMICS AND EFFECTS OF HEALTH STATUS ON LABOUR FORCE PARTICIPATION IN DELTA STATE - BUZUGBE, PATRICIA NGOZI (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
Nigeria faces a high and rising burden of disease. A high disease burden would potentially erode positive externalities from a viable labour force. Specifically, Delta State of Nigeria is relying on its labour force to achieve projected economic growth. Despite the potential negative labour market effect of illness and the rising disease burden in Delta State, there is limited empirical evidence on the relationship between self-reported illness and labour supply. This paper investigates the relationship between health conditions and labour force participation. A household survey in the 25 local government areas of Delta State provided the data. The study utilized a probit model and found that ill-health conditions reduce the likelihood of labour force participation. Ill-health conditions reduce the likelihood of labour force participation among women by a greater magnitude than among men. Therefore, the Delta State government should vigorously pursue effective policies and interventions to reduce the prevalence of ill-health conditions within the State.